Targeting DNA damage response components induces enhanced STING-dependent type-I IFN response in ATM deficient cancer cells and drives dendritic cell activation - Marta Lopez-Pelaez; Lucy Young; Mercedes Vazquez-Chantada; Nadine Nelson; Steve Durant; Robert W. Wilkinson; Edmund Poon; Miguel Gaspar; Viia Valge-Archer; Paul Smith; Simon J. Dovedi (OncoImmunology, 2022)
The concept of exploiting tumor intrinsic deficiencies in DNA damage repair mechanisms by inhibiting compensatory DNA repair pathways is well established. For example, ATM-deficient cells show increased sensitivity to the ATR inhibitor ceralasertib. DNA damage response (DDR)-deficient cells are also more sensitive to DNA damaging agents like the DNA crosslinker pyrrolobenzodiazepine (PBD) SG-3199. However, additional antitumor benefits from targeting the DDR pathways, which could operate through the activation of the innate immune system are less well studied. DNA accumulation in the cytosol acts as an immunogenic danger signal, inducing the expression of type-I interferon (IFN) stimulated genes (ISGs) by the activation of the cGAS-STING pathway. Here, we demonstrate that ATM −/− FaDu tumor cells have higher basal expression of ISGs when compared to WT cells and respond to ceralasertib and PBD SG-3199 by inducing higher levels of ISGs in a cGAS-STING-dependent manner. We show that sensitive tumor cells treated with ceralasertib and PBD SG-3199 activate dendritic cells (DCs) via a type-I IFN-dependent mechanism. However, STING deficiency in tumor cells does not prevent DC activation, suggesting that transactivation of the STING pathway occurs within DCs. Furthermore, depletion of the cytosolic DNA exonuclease TREX1 in tumor cells increases DC activation in response to PBD SG-3199-treated tumor cells, indicating that an increase in tumor-derived cytosolic DNA may further enhance DC activation. In summary, in this study, we show that ceralasertib and PBD SG-3199 treatment not only intrinsically target tumor cells but also extrinsically increase tumor cell immunogenicity by inducing DC activation, which is enhanced in ATM-deficient cells.